Comparison of internet-based versus paper-and-pencil administered assessment of positive development indicators in adolescents’ sample - Vosylis , Rimantas; Žukauskienė, Rita; Malinauskienė, Oksana (Psichologija, 2012)
The aim of this study was to evaluate the use of the online data collection method to survey adolescents about their psychological characteristics in a follow up-longitudinal study on positive youth development in order to test the psychometric equivalence of two assessment methods. 1030 participants (17–19 years old) completed paper-and-pencil questionnaires in schools (505 boys and 525 girls), 132 (28 boys and 104 girls) completed Internet-based questionnaires, and 47 (15 boys 32 girls) completed both, measuring positive development indicators. The findings suggest that adolescents report less socially desirable behaviour and active citizenship in Internet-based questionnaires, but generally Internet-based administration does not have any differences in the means values of positive development indicators as compared to paper-and-pencil administration. Internet-based questionnaires have higher or similar internal consistencies as compared with paper-and-pencil questionnaires and are highly correlated with each other when administered using Internet-based and paper-and-pencil assessment. There is no interaction effect of the Internet versus paper-and-pencil assessment and the sex of adolescents on the positive development indicators. Limitations of this study are discussed.